Comprehensive Evaluation of Environmental Policy for Water Pollutants Reduction in Jiaxing City, China - Feng Xu; Nan Xiang; Yoshiro Higano (European Regional Science Association (ERSA), 2012)
Recently, various environmental problems have been brought with the rapid economic development in China. Therefore, now it is important to enforce optimal environmental policies in order to achieve economic development as well as environmental improvement. In this study, we selected Jiaxing city as research area for its high water pollution problem combined with speedy economic growth, and we constructed integrated dynamic environmental-social economic system model to establish the optimization simulation. Through scenarios analysis, we can evaluate the efficiency of the environmental policies from the aspects of both environmental preservation and social economic development. This research will provide prediction on social-economic activities, such as production, finance and budget, endogenously in the social economic model, the water pollutants discharged from social economic activities in environmental system model in the region. The simulation results show a great improvement of the trade-off between environment improvement and economic development in Jianxing city, China.
Keywords: 330